2010
DOI: 10.1111/j.1365-2044.2010.06378.x
|View full text |Cite
|
Sign up to set email alerts
|

ORIGINAL ARTICLE: Ultrasonographic evaluation of the femoral vein in anaesthetised infants and young children

Abstract: SummaryWe investigated the cross-sectional area of the femoral vein and its relationship to the femoral artery at two anatomical levels, in infants and children. Sixty-six subjects were allocated to one of two groups: infants (< 1 year, n = 31) or children (1-6 years, n = 35). After induction of general anaesthesia, the femoral vein was evaluated by ultrasound with the patients' legs at 30°and 60°of abduction and their hips externally rotated. In each position, measurements were taken at the level of the ingui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
23
0
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 12 publications
4
23
0
2
Order By: Relevance
“…28 Most complications are associated to the multiple attempts to puncture the vessel with the needle to achieve cannulation. 14,27,29,30 The risk of complications significantly increases after two punctures of the same vessel, 28 and this increase is six times higher after three attempts. 30 Likewise, Ueda et al 31 conclude that a larger diameter is significantly associated to the success rate of a first attempt.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Most complications are associated to the multiple attempts to puncture the vessel with the needle to achieve cannulation. 14,27,29,30 The risk of complications significantly increases after two punctures of the same vessel, 28 and this increase is six times higher after three attempts. 30 Likewise, Ueda et al 31 conclude that a larger diameter is significantly associated to the success rate of a first attempt.…”
Section: Discussionmentioning
confidence: 99%
“…The same happens with cervical vessels, since the internal carotid artery can overlap the IJV or present these anatomical variations in relation to the internal carotid artery in as much as 54% of cases. 27 In comparison with the standard technique which uses anatomical landmarks, the use of ultrasound to cannulate central vessels in children reduces the number of attempts resulting in a lower complication rate. 28 Most complications are associated to the multiple attempts to puncture the vessel with the needle to achieve cannulation.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Iwashima et al, 25 citaron que la punción accidental de la AF ocurría en un 7% de los pacientes pediátricos cuando se utilizaba la ecografía, en relación con un 32% al hacerlo según la referencia anatómica. Esta tasa tan alta de punción arterial puede deberse, como apunta otro estudio realizado por Suk et al, 26 a las variaciones anatómicas que presentan los vasos, que pueden llegar a una tasa de superposición entre la arteria y la vena femoral en los niños de hasta un 74%. Igualmente ocurre en los vasos cervicales, ya que la arteria carótida interna puede superponerse a la VYI o presentar estas variantes anatómicas en su relación con la arteria carótida interna de hasta un 54%.…”
Section: Figura 2 Distribución De Las Canalizaciones Vasculares Ecogunclassified
“…However, studies have clearly shown that US-guided femoral vein cannulation can result in shorter cannulation times, than anatomical landmark-based cannulation. 4 The most common complication during femoral vein cannulation is femoral artery puncture, which may lead to arteriovenous fistula, pseudoaneurysm, hematoma, arterial thrombosis or peripheral embolism. 3 Moreover, pricking of the head of the femur may lead to avascular necrosis.…”
Section: Introductionmentioning
confidence: 99%
“…In this position, the cross-sectional area of the femoral vein is larger, and femoral artery overlapping is minimal. 4 The study was undertaken to evaluate whether US-guided femoral vein cannulation resulted in higher success rates…”
Section: Introductionmentioning
confidence: 99%